CLINICAL FEATURES OF COVID-19 AND ASSESSMENT OF THE HEALTH STATUS OF CHILDREN IN UFA WHO HAVE SUFFERED A NEW CORONAVIRUS INFECTION IN OUTPATIENT CARE - Регина Зинуровна Тихонова; Екатерина Серимжановна Кучина; Людмила Викторовна Яковлева (The Publishing House Medicine and Enlightenment, 2024)
The aim - to identify the clinical features of the course of COVID-19 and assess the health status of children who have had a new coronavirus infection during the last 6 months after infection. Materials and methods. On the basis of the «Children's Clinic № 5» in Ufa and «Children's Clinic № 3» in Ufa, 183 children aged 0 to 17 years who had COVID-19 from January 2022 to April 2023 were examined. Results. The new coronavirus infection was more often recorded in boys - in 61.2 % of cases, and in boys aged from 1 to 7 years - in 51.4 % of cases. The presence of a premorbid background was detected in 82,5 % of children; diseases of the nervous system prevailed - 31.1 % of cases and congenital heart anomalies - 27.8 % of cases. The leading clinical manifestations of COVID-19 were: fever - in 73.8 % of cases, weakness/lethargy and loss of appetite - in 65 % and 63.9 % of cases, cough - in 53.6 % of cases. The main manifestations of post-Covid syndrome: neurocognitive - in 51.4 % of children, pain in the heart area - in 43.2 % of children, loss of appetite - in 44.8 % of children. Mild anemia was recorded in 33.3 % of children. 70.5 % of children had pathological changes in the electrocardiogram: disturbances in repolarization processes - in 40.3 % of cases, sinus tachycardia - in 31 % of cases, atrioventricular block - in 10.8 % of cases. Conclutions. The leading clinical syndrome of post-Covid symptoms was asthenia, cardiac symptoms in the form of impaired repolarization processes, conduction, sinus tachycardia, mild anemia and a decrease in the level of resistance to acute respiratory diseases. It is necessary to carry out a minimum amount of research (CBC, OAM, ECG) in order to subsequently prescribe an individual program of treatment, preventive, rehabilitation measures and dynamic monitoring of the child's health after a coronavirus infection.